TINJAUAN KONDISI FISIK RENANG CLUB STADION DURI KABUPATEN BENGKALIS - Anggi Prawinoto; Saripin '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is carried out after this proposal is approved by the lecturers and lecturers at the time of the proposal seminar. The place of this research is carried out in the field Club Duri Swimming Club Bengkalis Regency. Durability Club athlete Duri Stadium Bengkalis Regency is in the category Poor Once is as many as 8 of 15 samples with the percentage of 53.33% .. Power Ledak Club athletes Duri Stadium Bengkalis District is in the category of less that as many as 11 people and the percentage of 73, 33%. The formation of Club athlete Stadium Duri Bengkalis Regency is in the Very Good category once is as many as 12 people and the percentage of 80%. Agility Clubs Duri Bengkalis Stadium is located in the Medium category of 12 people and the percentage of 80%. Physical Conditions Club athletes Duri Stadium Bengkalis District is in the category of Less is in the percentage of 71.67%.Keywords: Physical Condition, Swimming